The Latinx Guide to Graduate School - Negrón-Gonzales, Genevieve; Barrera, Magdalena L., 1975- (Book collections on Project MUSE., 2023)
"The Latinx Guide to Grad School offers readers advice on the graduate school process-from the application stage to the cultivating of effective networks in academia-in an accessible guidebook. It provides a broader institutional analysis as well as grounded advice for prospective and current graduate students navigating doctoral and Master's programs, with a specific focus on the humanities and social sciences, areas of study with significant Latinx representation. Genevieve Negrón-Gonzales and Magdalena L. Barrera have worked for many years as professors, thesis advisors, dissertation chairs, instructors, and mentors within institutions with a large percentage of Latinx undergraduate and graduate students. They identify common challenges, key questions, and helpful techniques for supporting Latinx students that will be helpful for both students and faculty mentors. This book offers their refined approaches to working with Latinx students in a way that both pushes them forward in their work and academic goals in an ethical, socially-engaged manner that still offers a critical assessment of institutions of higher education"--